A randomized controlled trial to evaluate the efficacy of metacognitive training for people with schizophrenia applied by mental health nurses: study protocol - Pinho, Lara Manuela Guedes de (2021)
Aim To evaluate the efficacy of the Portuguese version of the metacognitive training (MCT) programme for schizophrenia and its effects on psychotic symptoms, insight into the disorder and functionality.